Organizational Best Practices for Transportation Projects Delivered Using Alternative Contracting Methods - Gransberg, PhD, PE, Douglas D.; del Puerto, PhD, Carla Lopez; Tapia, PhD, PMP, Ricardo M. (KnE Engineering, 2018)
The use of Alternative Contracting Methods (ACM) to deliver US transportation projects has reached a point where a definitive set of best practices can be identified to leverage the lessons learned by early ACM adopters. The most pressing need is for guidance on how public agencies organize to implement ACMs in a budget-constrained environment where the possibility of increasing the number of public agency engineers is nil. This paper is based on mining the survey response data from 6 National Cooperative Highway Research Program (NCHRP) synthesis reports on ACM topics and proposes a framework for analyzing ACM practices deemed effective by peer-reviewed research to determine if each practice can be classified as a best practice. Importance index theory provides the analytical foundation for the framework and provides a ranking of candidate best practices in order of each practice’s importance and effectiveness. Nine effective ACM practices were identified and evaluated with only one, “appointing an agency ACM champion,” meeting the objective criteria for a best practice. The paper’s major contribution is to provide the suite of 1 best and 8 effective practices that can be employed when developing the organization for an agency that has decided to implement ACM project delivery. Keywords: Alternative contracting methods, best practices, organizational structure, index number theory.